1990
DOI: 10.1002/jbmr.5650051381
|View full text |Cite
|
Sign up to set email alerts
|

Journal of Bone and Mineral Research

Abstract: It is not clear to what extent the increased bone mass observed in vertebral trabecular bone of fluoride-treated mammals is a consequence of effects of fluoride on the number and activity of osteoclasts or of osteoblasts. In the present communication, we have analyzed the effects of NaF on the activity of isolated rabbit osteoclasts cultured on thin slices of devitalized compact bovine bone. Osteoclastic resorption was quantitated by counting the number of resorption lacunae and measuring their surface area an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 16 publications
(6 reference statements)
1
22
0
1
Order By: Relevance
“…19 Fluoride can inhibit the function of isolated osteoclasts at 0.5 to 1.0 mmol·L −1 in vitro . 20 Fluoridated drinking water markedly inhibited the bone resorption induced by hydrocortisone 21 and showed a lower histologic incidence of alveolar bone resorption after the injection of parathormone. 22 …”
Section: Discussionmentioning
confidence: 91%
“…19 Fluoride can inhibit the function of isolated osteoclasts at 0.5 to 1.0 mmol·L −1 in vitro . 20 Fluoridated drinking water markedly inhibited the bone resorption induced by hydrocortisone 21 and showed a lower histologic incidence of alveolar bone resorption after the injection of parathormone. 22 …”
Section: Discussionmentioning
confidence: 91%
“…4 It has been shown that fluoride reduced the number of the osteoclasts in bone. 24 Additionally, it has been demonstrated that fluoride decreases the number of resorption lacunae made by individual clast cells, 25 the resorbed area per clastic cells, 16,19,25 and the depth of the clastic cell demineralization pit. 16,19,26 In the present study, high fluoride groups exhibited a decreased amount of root resorption after the application of light and heavy forces for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…As these findings are similar to the clinical syndrome of skeletal fluorosis in humans, a pathogenic mechanism has been suggested whereby chronic daily consumption of trifluorinated voriconazole molecules leads to excess plasma fluoride, which then promotes the development of periostitis by enhancing the activity of osteoblasts (11,13,17). Although this is consistent with the known clinical and cellular effects of fluoride (19,20,31,32,40), this hypothesis has not been directly evaluated for voriconazole-associated periostitis. Therefore, the goal of this study was to evaluate this hypothesis by assessing the effects of voriconazole exposure on osteoblastic activity in vitro.…”
Section: Discussionmentioning
confidence: 98%
“…Given that bones sequester fluoride over the human life span, it is possible that voriconazole stimulates fluoride release from bone. While fluoride has been demonstrated to inhibit osteoclastic activity in proportion to its concentration (40,45,46), to our knowledge no studies have examined the effects of voriconazole on osteoclasts.…”
Section: Discussionmentioning
confidence: 99%